The Challenges Encountered by Lecturer in Translanguaging Practices in Morphosyntax Subject of English Language Education Program - Ni Putu Anggi Natalia Sugita; Ni Made Ratminingsih; Ni Wayan Surya Mahayanti (Tell : Teaching of English Language and Literature Journal, 2025)
Translanguaging has emerged as a pedagogical approach that facilitates multilingual learners in the EFL higher education. While studies have extensively explored its benefits, limited study has examined the challenges encountered when implementing translanguaging in specific content area, such as Morphosyntax. This study addresses this gap by investigating challenges faced by a lecturer in translanguaging practices in an undergraduate of the English Language Education program. This research was belonged to qualitative research using a semi-structured interview. Based on the preliminary research, it showed that the lecturer applied translanguaging during the teaching and learning process. A semi-structured interview was conducted for 11 meetings to obtain data regarding the challenges confronted by the lecturer. The data were analyzed through a deductive thematic analysis to acquaint the objective of the research. The challenges of translanguaging were categorized into 3 aspects; situations, tasks, and problems. The findings revealed that during translanguaging practices in 3 learning phases, the lecturer did not encounter any significant challenges. Instead, the lecturer found that translanguaging practices had facilitative function to assist students in achieving the learning objectives. Therefore, this research elucidated the information about translanguaging practices as an approach that can be implemented in the English language teaching and learning.